Thermal stability optimization of single-leg skutterudite-based thermoelectric devices based on lattice distortion effects - Hui Pan; Zhan Sun; Huiyuan Geng; Qing Chang; Bo Zhang; Lixia Zhang (Journal of Materiomics)
Skutterudite-based (SKD-based) thermoelectric materials are well-known for their high figure-of-merit (zT value) in the intermediate temperature region. Based on the urgent need for long-term high-temperature service, the poor interfacial thermal stability when connected with the Cu electrodes has greatly limited its industrial application. In this work, we propose a novel alloying route for the barrier layers for p-type SKDs. A Fe80Cr17.5Mo2.50/p-SKD junction with matched coefficients of thermal expansion (CTE), high mechanical reliability, and low contact resistivity is obtained. The addition of large-scale Mo causes severe lattice distortion in the barrier alloy, which contributes to the sluggish elemental diffusion. Thus, after aging at 823 K for 600 h, the Fe80Cr17.5Mo2.5 junction has a thinner reaction layer (∼25 μm), lower contact resistivity (∼3.8 μΩ·cm2), and higher shear strength (∼14 MPa), compared with the Mo-free (Fe80Cr20) barrier junction. Our finding opens a new insight for fabricating long-term high thermally stable SKD-based thermoelectric devices with desirable mechanical stability.